Alvespimycin Exhibits Potential Anti-TGF-β Signaling in the Setting of a Proteasome Activator in Rats with Bleomycin-Induced Pulmonary Fibrosis: A Promising Novel Approach - Osama A. Mohammed; Mustafa Ahmed Abdel-Reheim; Lobna A. Saleh; Mohannad Mohammad S. Alamri; Jaber Alfaifi; Masoud I. E. Adam; Alshaimaa A. Farrag; AbdulElah Al Jarallah AlQahtani; Waad Fuad BinAfif; Abdullah A. Hashish; Sameh Abdel-Ghany; Elsayed A. Elmorsy; et al. (MDPI AG, 2023)
Idiopathic pulmonary fibrosis (IPF) is an irreversible and life-threatening lung disease of unknown etiology presenting only a few treatment options. TGF-β signaling orchestrates a cascade of events driving pulmonary fibrosis (PF). Notably, recent research has affirmed the augmentation of TGF-β receptor (TβR) signaling via HSP90 activation. HSP90, a molecular chaperone, adeptly stabilizes and folds TβRs, thus intricately regulating TGF-β1 signaling. Our investigation illuminated the impact of alvespimycin, an HSP90 inhibitor, on TGF-β-mediated transcriptional responses by inducing destabilization of TβRs. This outcome stems from the explicit interaction of TβR subtypes I and II with HSP90, where they are clients of this cellular chaperone. It is worth noting that regulation of proteasome-dependent degradation of TβRs is a critical standpoint in the termination of TGF-β signal transduction. Oleuropein, the principal bioactive compound found in Olea europaea, is acknowledged for its role as a proteasome activator. In this study, our aim was to explore the efficacy of a combined therapy involving oleuropein and alvespimycin for the treatment of PF. We employed a PF rat model that was induced by intratracheal bleomycin infusion. The application of this dual therapy yielded a noteworthy impediment to the undesired activation of TGF-β/mothers against decapentaplegic homologs 2 and 3 (SMAD2/3) signaling. Consequently, this novel combination showcased improvements in both lung tissue structure and function while also effectively restraining key fibrosis markers such as PDGF-BB, TIMP-1, ACTA2, col1a1, and hydroxyproline. On a mechanistic level, our findings unveiled that the antifibrotic impact of this combination therapy likely stemmed from the enhanced degradation of both TβRI and TβRII. In conclusion, the utilization of proteasomal activators in conjunction with HSP90 inhibitors ushers in a promising frontier for the management of PF.